CLINICAL AND ELECTROENCEPHALOGRAPHIC SEMIOLOGY OF MYOCLONIC-ATONIC SEIZURES - M. B. Mironov; K. Yu. Mukhin; T. M. Krasilschikova; A. F. Dolinina; A. S. Petrukhin (Эпилепсия и пароксизмальные состояния)
Abstract: myoclonic-atonic seizures (MAS) – short epileptic generalized seizures in the form of sudden falling spells (or drop attacks). Inour study were vealed MAS in 1.3% of all cases of epilepsy with onset of seizures before 18 years old (n=1261). Predominance of man among the patients was revealed (76.5% men versus 23.5% woman). The most often in the patients with MAS myoclonic-astatic epilepsy (MAE) was diagnosed – 41,2% of cases. Symptomatic and cryptogenic forms of focal epilepsy were diagnosed in 35.2% of the patients. Lennox-Gastaut syndrome was revealed in 23.6% of cases. Onset of epilepsy with MAS varied widely – from 9 month to 6 year soflife; middle age of onset was 3.4 years±1.28 years. In all the cases MAS occurred in combination with other types of seizures: there can be any of 9 differenttypes of seizures. The most often myoclonic seizures (70.6% of cases), generalized convulsive seizures (47.1%) and absences (47.1%) were registered. Remission was achieved in 64.7% cases of epilepsy, associated with MAS. Reduction of seizure frequency ≥50% on antiepileptic treatment was achieved in 29.4% of the patients. Only in one patient (5.9%) the therapy was not effective. Our study demonstrated different efficacyof antiepileptic drugs in the treatment of different epileptic syndromes, associated with MAS.